The effect of slaughter weight and fattening intensity on changes in carcass fatness in young Holstein-Friesian bulls - Zenon Nogalski; Zofia Wielgosz-Groth; Cezary Purwin; Anna Nogalska; Monika Sobczuk-Szul; Rafał Winarski; Paulina Pogorzelska (Italian Journal of Animal Science, 2014)
The objective of this study was to determine the effect of body weight (BW) at slaughter and fattening intensity on carcass fatness and meat fatty acid profile in young Holstein- Friesian bulls. One-hundred bulls fattened on two levels of intensity a semi-intensive (SI) and an intensive (I) were used. Fattening was carried out to BW of 500, 550, 600, 650 and 700 kg. Live ultrasound measurements were performed to determine back fat thickness. Carcass dressing percentage, carcass conformation and fatness, intramuscular fat content of m. longissimus dorsi and fatty acid profile (by gas chromatography) were determined after slaughter. Intensively fattened bulls were characterised by a greater carcass dressing percentage – by 1.17% on average, greater carcass conformation scores, greater external fat thickness and a greater intramuscular fat content than bulls SI fattened. Fat from intensively fattened bulls contained higher levels of polyunsaturated fatty acids (PUFAs) – by 0.96/100 g on average. Semi-intensive fattening contributed to a decrease in the n-6/n-3 PUFA ratio and to a significant increase in the concentrations of C18:2 and C20:4 fatty acids. Regardless of the fattening intensity, the n- 6/n-3 ratio was greater in heavier animals. The best results were achieved when young Holstein-Friesian bulls were fattened intensively to BW of 650 kg.